TERAPI AGAMA TERHADAP PROBLEMATIKA JIWA MANUSIA - Moh. Nurdhuka (Jurnal Studi Islam dan Sosial, 2018)
Religious psychology studies mental problems that are related to one's religious beliefs. When humans try to cure psychiatric disorders through religious teachings, because religion offers a transcendental relationship to things through worship and religious ceremonies that provide an emotional basis for a stronger sense of security and identity amid the uncertainty and impossibility that humans experience in their lives. Psychology and religion are two different elements, but both are closely related and affect humans in attitude and behaving. Due to the way to behave, think and behave a person cannot be separated from his beliefs, because the beliefs he has are included in the personality section.